FcγRIIIa is a noncanonical costimulatory molecule for CD8 T cells - Kevin S. Kao; Nicole L. Pihlstrom; Emily G. Niejadlik; Tineke Cantaert; Rafi Ahmed; Jeffrey V. Ravetch; Stylianos Bournazos (Proceedings of the National Academy of Sciences, 2025)
A critical component of the function of IgG antibodies is their capacity to engage specialized cellular receptors, Fcγ receptors (FcγRs), expressed on effector leukocytes. Highlighting the importance of FcγR-mediated signaling in the regulation of the fate, activation, and differentiation status of leukocytes, FcγRs are ubiquitously expressed by nearly all leukocyte populations. Here, we report that while at steady state, T cells are negative for all classes of FcγRs, CD8 T cells specifically induce the expression of the activating FcγR, FcγRIIIa, in response to viral infection in cohorts of COVID-19 and dengue patients, as well as in virus infection models using FcγR humanized mouse strains. In in vivo mechanistic studies, we demonstrate that induction of FcγRIIIa expression on effector CD8 T cells follows a well-defined trajectory that closely tracks the course and magnitude of the immune response, while immune resolution is characterized by receptor downregulation. Uniquely to these CD8 T cells, FcγRIIIa crosslinking alone is paradoxically insufficient to elicit T cell activation and cytotoxicity. However, when coupled with T cell receptor (TCR) stimulation, it results in synergistic cellular activation and, compensates for the downregulation of canonical costimulatory molecules on terminal effector CD8 T cells. These results reveal a previously unappreciated role for FcγRIIIa as a unique costimulatory molecule that synergizes with TCR signaling to lower the effective threshold required for CD8 T cell activation, highlighting the role of virally induced antibodies in modulating CD8 effector cell responses.